“The Way of Disc Dog”: Navigating Harmonies in American Canine Frisbee - Jack Harrison; Sara Kruszona (European Journal of American Studies)
Freestyle disc dog is a sport in which a human handler throws frisbees for their dog to catch as part of a choreographed routine to music. In this article, we examine how different representations of ideal dog–human relations in media produced and consumed by American disc-dog players correspond to concepts of harmony. Drawing on philosophical writing about dog–human relations in the works of Vicki Hearne and Donna Haraway, the article argues that ideal ways of “fitting together,” both on and off the disc-dog field, navigate competing visions of dog–human harmony in the US. An analysis of training handbooks, competition rules, online video interviews with American handlers, and footage of disc-dog training sessions and competitions identifies the best interspecies players harmoniously interacting both as predesigned, routinized parts of a predetermined whole and as entities who are open to being transformed by one another in the emergence of dynamic, unpredictable play. However, ways of experiencing and evidencing a successful partnership in disc dog—which includes “connecting” with one’s dog, performing a difficult routine, and having fun with both one’s canine partner and the audience—are not so easily aligned and often rub up against one another. This navigation of different concepts of harmony, we conclude, underpins a particular vision of dogs as straddling various forms of ideal canine-ness for American handlers.